DESCRIPTION OF SMELL IN NOVEL PALRFUME THE STORY OF MURDERER BY PALRTRICK SUSKIND - Ramadani, M. Renaldi; Nur, Riola Haya; Nur, Muh. Safar (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
Literalture is al waly thalt people use words to shalre feelings alnd show life. It often tells stories using things from everydaly life. AL novel is al type of story thalt malny people enjoy realding. It often uses words to represent deeper ideals alnd feelings. Paltrick Suskind's